PakCu 916: the entrepreneurial pursuit of two generations / Mohd Ali Bahari Abdul Kadir ... [et al.] - Abdul Kadir, Mohd Ali Bahari; Rosly, Hardi Emrie; Rahim, Hardy Loh; Junid, Junainah; Mohd Lajin, Noor Faizah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
This case study looks upon the entrepreneurship journey of PakCu and his second-generation successors in starting up their business called PakCu 916. From a mere roadside stall focusing on selling cut fruit (guava), they were able to expand to more than 400 outlets within a year. With yearly sales of around an RM4million, they were heading into a bright future. However, unexpected problems arose concerning their "licensees," rising costs, good and services tax (GST), account receivables, rental, and layoffs. Therefore, they considered exiting their licensing business with 480 stalls to diversify their business to ready-to-drink (RTD) products to be sold in hypermarkets. However, this comes with its hurdles as most hypermarkets are not so accepting due to their strict terms and conditions and the high slotting fees needed to pay to place their product on the shelves.